A social marketing plan using new media healing hands center foundation - Pabiona, Kristine Judy Maricel J.
The Healing Hands Center Foundation is a non-profit organization which promotes positive outlook towards children diagnosed to have autism. ADHD, Cerebral Palsy and other related physiological and neurological disorders. However, despite the positive drive to render full services to the masses, the HHCF remains a low-profile, low-funding organization. Thus, this study was created to address the HHCF's publicity problems by creating a Social Marketing Plan Using the New Media. Publicity plays a critical role in marketing and promotions for organizations such as the Healing Hands Center Foundation. Publicity information about an event, an individual or group, or a product ? appears a news item or feature story in the mass media. To achieve the objective, the researcher went through the whole process of hands-on publicity strategies. First, was the redesigning and reactivation of the HHCF multiply page followed by a creation of the HHCF twitter account. The researcher went through the linking process of the three social network accounts (Facebook, Twitter and Multiply) wherein improvements were sought through Facebook Fanpage Insights, containing the HHCF Users Graph, Daily Active Users and New Likes graphs, Demographics of active users, activities of the active users summarizing wall, photos, reviews and discussion boards. Another improvement was sought in multiply viewing history wherein there is an increase in the number of viewers. It was observed that the operation was highly effective even for just a short period of time. However, there was an immediate decrease in the number of interaction when there is no update. Thus the creation of the Social Marketing Plan Using the New Media was advised wherein objective, situation analysis, competitive analysis, major goal, target markets, strategies, marketing team, tactical timeline and ideas for internal promotion were taken into consideration. At the end of the study, the researcher was able to conclude that the presence in the internet makes an organization more known to the general public. It also improved the number of patron and of course, improved publicity. The graphs prove that the interaction among HHCF and online users are becoming more active thus, promoting the internet presence of the HHCF, and of all these will be maximized through the Social marketing Plan Using the New Media. The whole process also contributed in the search Engine Optimization of the Healing Hands Center Foundation.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media Arts